ON THE CALCULATION OF IMPLIED VOLATILITY - EVITA DEWI (NIM: 20107008), KANIA
This study is intended to calculate implied volatility of a stock by genetic algorithm and Newton-Raphson method. Genetic algorithm, a method of solving optimization problem, does not require the characteristic of function to solve, it can solve many mathematic problems as long as they can be changed into optimization problem. In this study, the result of calculation of genetic algorithm is compared to that of Newton-Raphson method.